The Patient's Experience of the Psychosocial Process That Influences Identity following Stroke Rehabilitation: A Metaethnography. (5th December 2013) - Hole, E.; Stubbs, B.; Roskell, C.; Soundy, A.
Abstract : Background and Purpose. Patient experience is increasingly being recognised as a key health outcome due to its positive correlation with quality of life and treatment compliance. The aim of this study was to create a model of how patient's experiences of rehabilitation after stroke influence their outcome. Methods. A metaethnography of qualitative articles published since 2000 was undertaken. A systematic search of four databases using the keywords was competed. Original studies were included if at least 50% of their data from results was focused on stroke survivors experiences and if they reflected an overarching experience of stroke rehabilitation. Relevant papers were appraised for quality using the COREQ tool. Pata analysis as undertaken using traditional processes of extracting, interpreting, translating, and synthesizing the included studies. Results. Thirteen studies were included. Two themes (1) evolution of identity and (2) psychosocial constructs that influence experience were identified. A model of recovery was generated. Conclusion. The synthesis model conceptualizes how the recovery of stroke survivors' sense of identity changes during rehabilitation illustrating changes and evolution over time. Positive experiences are shaped by key psychosocial concepts such as hope, social support, and rely on good self-efficacy which is influenced by both clinical staff and external support.